Evaluation of Functional and Biomechanical Deficiency in the Shoulder Joint: a Prospective Cohort Study of 119 Patients with Rotator Cuff Injury - Vasiliy A. Kolyshenkov; Anatoliy D. Fesyun; Maxim Y. Yakovlev (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2023)
AIM. To assess the degree of change in functional and biomechanical characteristics of the shoulder joint in patients with rotator cuffinjury.MATERIAL AND METHODS. The study included 119 patients, 59 patients with rotator cuff injury and 60 practically healthy volunteerswith no history of injuries and shoulder disorders, aged 18 to 66 years. All patients completed DASH questionnaires and underwentclinical examination by a traumatologist, neurologist and physical therapist, as well as a biomechanical examination of the shoulderjoint. The biomechanical parameters of the shoulder joint were studied using the «Con-Trex MJS» (Physiomed, Germany) computerizedisokinetic dynamometer. We chose the inward/outward rotation test as the diagnostic test. The inward/outward rotation test wasperformed lying on the back. The elbow was bent at an angle of 90º, the upper limb was moved 90º at the shoulder joint. The handle ofthe dynamometer was set individually according to the patient's limb length. The axis of rotation of the dynamometer coincided withthe axis of rotation in the shoulder joint. The maximum allowable amount of motion in the test was limited to 90º movement of theexternal rotation and 80º internal rotation. The neutral position of the shoulder joint retraction equal to 90 ° and the elbow joint flexionat 90 ° were taken as the zero point of reference.RESULTS AND DISCUSSION. Patients with rotator cuff injury have a high shoulder pain level, 6.00 [5.00;7.00] VAS, a severe degree offunctional limitations 63.33 [55.92;66.67] scores on the DASH questionnaire, a pronounced decrease in shoulder range of motions, aswell as a significant deficit in dynamic strength and endurance indices and muscle performance.CONCLUSION. Patients with shoulder rotator cuff injury experience extensive functional limitations expressed in a high level of pain inthe shoulder joint, high points of the questionnaire of the upper limb functioning (DASH, more - worse) and a significant decrease inthe biomechanical indicators of the shoulder joint and upper limb in general, which ultimately leads to a serious limitation of functionalactivity, a decrease in the working capacity and, consequently, a decrease in the quality of life.